The Impact of Enculturation on Child-Rearing Practices: A Comparative Study between Asia and Europe - Utaminingsih, Diah; Haenilah, Een Yayah; Mujiyati; Nurwahiddin, Muhammad; Sinaga, Risma Margareta; Adha, Muhammad Mona (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article investigates the influence of enculturation on child-rearing practices across Asian and European cultures. Enculturation the process through which individuals internalize the values, norms, and practices of their culture plays a crucial role in shaping parenting strategies. In Asia, parenting is primarily shaped by religious values and collectivist principles, resulting in structured and community-based child-rearing approaches. In contrast, European parenting tends to emphasize individualism, nurturing children’s independence and appreciation for cultural diversity. Despite these differences, both regions recognize the vital role of culturally and religiously sensitive education in fostering children’s character and behavior. Findings indicate that children raised in culturally enriched environments exhibit stronger emotional stability and intellectual development. Asian parenting supports social cohesion through communal support systems, while European approaches promote critical thinking and adaptability. These insights highlight the need for culturally informed educational programs and parenting policies that address the specific socio-cultural contexts of each region. Future research is recommended to explore enculturation among minority or immigrant families, the effects of bicultural parenting, and how global cultural shifts influence parenting norms across generations.